(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The current study aims to identify the morphological description and histological structure of kidney in bird. Morphologically the kidney consist of three lobes represented by the cranial, medial and caudal taking into account the difference in the shape and size of the lobes. According to histology, the kidney is surrounded in a delicate connective tissue capsule. The kidney’s primary structural component is the lobule, which is made up of cortical and medullary tissue in each lobule. There are two parts to the kidney medulla and cortex. The cortex is larger than the medulla and has glomeruli, proximal convoluted tubules, and distal convoluted tubules, whereas the medulla has thin and thick segments of Henle’s loop, collecting tubules, and collecting ducts. Conclusion: The kidneys in Iraqi birds are morphologically and histologically different.